Tandem surface engineering of graphene quantum dot-assisted fluorinated NiFe Prussian blue analogue for electrocatalytic oxygen evolution reaction - Tarigan, Angelina Melanita; Aulia, Sofiannisa; Rinawati, Mia; Chang, Ling-Yu; Cheng, Yao-Sheng; Chang, Ching-Cheng; Huang, Wei-Hsiang; Chen, Jeng-Lung; Setyawan, Heru; Yeh, Min-Hsin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •A novel surface engineering strategy via GQD-assistance electrocatalysts has been established.•The metal activation by GQD through the higher transition metal interaction was explored.•Synergistic interaction of F ions and GQD on PBA matrix significantly enhances the OER performance.•GQD/F-NiFe PBA exhibits better electrocatalytic OER performance of 318 mV at 50 mA cm−2. Electrolytic water splitting for hydrogen has rapidly developed along with the increasing necessity for clean energy resources. Meanwhile, the obstacle originating from the slow 4-electron-involved oxygen evolution reaction (OER) pushes the urgency to create efficient, durable, earth-abundant electrocatalysts. As one of the promising candidates, it remains a challenge to enhance the reactivity of the Prussian-blue analogue (PBA) towards the OER. Herein, we propose a unique tandem surface reconstruction strategy for NiFe PBA followed by heteroatomic F doping and graphene quantum dot (GQD) decoration to modify the surface chemistry. GQD could improve electrocatalytic performance through the higher transition metal interaction with NiFe PBA due to the distinct electronic structures and an abundance of edge sites. X-ray absorption spectroscopy (XAS) revealed that F- ions were more likely to affect metal bonds. In contrast, GQD plays a role in modifying the metal states through the higher transition metal interaction. The proposed GQD/F-NiFe PBA with tandem surface engineering demonstrated promising electrocatalytic activity for OER in an alkaline medium, with an overpotential of 318 mV at a current density of 50 mA cm−2 and a small Tafel slope of 34.7 mV dec-1. The proposed tandem surface engineering for modifying PBA-based material surfaces represents a novel approach to designing advanced electrocatalysts.